IDENTIFIKASI ASPEK ALAT DAN ARTEFAK KULTURAL DALAM DAKWAH SUNAN KALIJAGA - Elfara Hajjar Sujani; Mahmud Arif (IAIN Syekh Nurjati Cirebon, 2021)
Sunan Kalijaga is one of the famous and influential Wali Songo in Java. As a preacher, Sunan Kalijaga spread Islam from one area to another. The Islamization process was carried out by Sunan Kalijaga does not force people to abandon the culture and beliefs they have embraced, but is carried out with an interesting approach and the islamitation procces followed the customs that exist in the area. The cultural approach taken includes various aspects, ranging from music, vocal arts to fine arts. The da'wah carried out by Sunan Kalijaga on the island of Java has produced a lot of various cultural tools and artifacts that have an influence not only on Muslims, but also it becomes Indonesian cultural relics that are dissolved to this day. Puppets, gamelan, suluk, modifications of surjan to agricultural tools are tools that are a legacy of Sunan Kalijaga which are still easy to find. Mosques and tombs in the city of Demak become one of the pilgrimage destinations for Muslims, which shows that Sunan Kalijaga has a great influence to this day.